(3fUGH GdEMJSGHs - (3YeQ Hf eMeO Hf YhV GdTGej GdMfaj GdSfGej,J (B696 (3g` s ((3YHjO Gddg Hf eUWai Hf eQJVi s)
(3ChdgG (B:s
(3GdMeO ddg GdMSjH GdbQjH Ydi fhGdg eSGFd ENJUJ HGdfSHI Edi MSH efUH GdMSHI ef cJH eYJHQI Hjf GdabgGA hgj eQJHI Ydi CHhGH GdHGH GdChd ai JaSjQ GddaXjf GdeJOGhdjf ai gPG GdcJGH s
(3BNQgG (B:s
(3dCf YeQ QVi Gddg Yfg CNQL CNJ CHj HcQ ef HjJg Mjf fGMJ Ydjg ef UMjM GdHNGQi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1953s
Keywords: (3Gdabg GdMfajs